Single-step selective laser writing of flexible photodetectors for wearable optoelectronics - An, Jianing (2018)
The increasing demand for wearable optoelectronics in biomedicine, prosthetics, and soft robotics calls for innovative and transformative technologies that permit facile fabrication of compact and flexible photodetectors with high performance. Herein, by developing a single‐step selective laser writing strategy that can finely tailor material properties through incident photon density control and lead to the formation of hierarchical hybrid nanocomposites, e.g., reduced graphene oxide (rGO)–zinc oxide (ZnO), a highly flexible and all rGO–ZnO hybrid‐based photodetector is successfully constructed. The device features 3D ultraporous hybrid films with high photoresponsivity as the active detection layer, and hybrid nanoflakes with superior electrical conductivity as interdigitated electrodes. Benefitting from enhanced photocarrier generation because of the ultraporous film morphology, efficient separation of electron–hole pairs at rGO–ZnO heterojunctions, and fast electron transport by highly conductive rGO nanosheets, the photodetector exhibits high, linear, and reproducible responsivities to a wide range of ultraviolet (UV) intensities. Furthermore, the excellent mechanical flexibility and robustness enable the photodetector to be conformally attached to skin, thus intimately monitoring the exposure dosage of human body to UV light for skin disease prevention. This study advances the fabrication of flexible optoelectronic devices with reduced complexity, facilitating the integration of wearable optoelectronics and epidermal systems.